Analyzing the tank barge market in the ARA - Rhine region. Issue 2 (June 2020) - van Hassel, Edwin; Rashed, Yasmine
Abstract: The inland tanker sector in the Antwerp - Rotterdam - Amsterdam (ARA) -Rhine region has the newest and most modern inland tankers in the world of shipping sector. The sector is characterized by a dynamic and a volatile market on both the demand and the supply sides. On the supply side, the market is dynamic with many new and large tank barges that are added to the fleet. Moreover, the total tank barge market is characterized by high volatility on the supply side (due to fluctuating water levels on the river Rhine). On the demand side, the demand is derived from two main sub-sectors. The first one is the mineral sector (crude oil, fuels and fuel derivatives), and the second one is the chemical sector. Hence, the volatility in demand arises from the fuel trade trends and the crude oil price. The main objective of this paper is to provide an insight into the inland tank barge sector and to identify the factors that are impacting the transport volume of the tank barge sector by means of an error correction model (ECM). Moreover, a forecast for the potential demand is made based on 3 scenarios.